(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This study examines the burgeoning potential of food tourism in Calabar, the capital city of Cross River State, Nigeria. Known for its rich culinary heritage and vibrant cultural scene, Calabar offers a unique blend of traditional Efik dishes, immersive food-related activities, and iconic events such as the Calabar Carnival. Employing a mixed-method approach, the research explores tourist awareness and perceptions of indigenous foods, the economic contributions of food tourism, and the role of cuisine in preserving cultural identity. The findings reveal a strong appreciation for Calabar’s culinary offerings, with tourists valuing their freshness, flavor, and cultural significance. However, challenges such as inadequate infrastructure, inconsistent promotion, and hygiene concerns limit the sector’s full potential. This study advocates for targeted investments in infrastructure, marketing, and capacity building to position Calabar as a premier culinary destination in Africa, fostering sustainable tourism and economic growth